2020
DOI: 10.18038/estubtda.724450
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Spaceborne Nitrogen Dioxide Over Turkey

Abstract: As a reason for a pandemic, the global novel COVID-19 virus has affected all of the World and caused lockdowns in many countries. Naturally, with decreased anthropogenic activities, the influence of the people over the environment has declined. Thus, improvement in air quality has been noticed. With the use of remote sensing data, in this short communication, we observed the Nitrogen Dioxide (NO2) over Turkey in the first month from the first appearance of the virus. Then, we compare the results with the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
2
6
0
1
Order By: Relevance
“…The analysis showed that the six Emirates experienced a decline in NO 2 levels because of restricted transportation and factories' closure. This result is compatible with other earlier studies undertaken in various regions around the globe ( Baldasano, 2020 ; Dantas et al, 2020 ; Islam et al, 2020 ; Kaplan and Avdan, 2020 ; Sharma et al, 2020 ). Fig.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The analysis showed that the six Emirates experienced a decline in NO 2 levels because of restricted transportation and factories' closure. This result is compatible with other earlier studies undertaken in various regions around the globe ( Baldasano, 2020 ; Dantas et al, 2020 ; Islam et al, 2020 ; Kaplan and Avdan, 2020 ; Sharma et al, 2020 ). Fig.…”
Section: Resultssupporting
confidence: 94%
“…Likewise, during the COVID-19 pandemic, many other recent studies show a significant decline in the level of air pollutants such as NO 2 , SO 2 , PM 10 , PM 2.5 , CO, etc. globally ( Archer et al, 2020 ; Collivignarelli et al, 2020 ; Dantas et al, 2020 ; Islam et al, 2020 ; Kaplan and Avdan, 2020 ; Kerimray et al, 2020 ; Nakada and Urban, 2020 ; Ranjan et al, 2020a ; Wang and Su, 2020 ). However, while studies generally showed a reduction in the primary pollutants, some studies showed no reduction in air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, considering the results of other towns the NO2 values has declined during lockdown and presents the improvement in air quality. Therefore, in support of this result, several studies have been reported globally (Aloi et al, 2020;Bao and Zhang, 2020;Bashir et al, 2020;Kerimray et al, 2020;Kaplan and Avdan, 2020;İban, 2020).…”
Section: No2 Assessment In March 2019 and March 2020supporting
confidence: 59%
“…The NO 2 reductions were found to be 20-30 % in Wuhan, China, Europe, Italy, France, Spain, and USA following lockdown periods ( NASA 2020 , ESA 2020 ). Kaplan and Avdan (2020) investigated the effect of COVID-19 on NO 2 concentration in Turkey during the March 15-April 15 periods in 2019 and 2020. They reported that the mean concentration of NO 2 was found to be in the range of 50 to 220 µmol/m 2 in 2019, it was in the range of 40 to 135 µmol/m 2 during COVID-19 period in 2020.…”
Section: Resultsmentioning
confidence: 99%